Partição de recursos alimentares entre espécies de Astyanax do baixo Rio Iguaçu, Paraná, Brasil - PINI, Suelen Fernanda Ranucci (2015)
The fish species occuring in the same area should be studied in order to check which ecological differences allow this coexistence. Thus, the aim of this study was to determine whether the species of the Astyanax from Lower Iguaçu River (downstream of the Salto Caxias Reservoir), belong to various trophic groups, and consume proportions of different food resources, allowing coexistence. For that, collections were made monthly from September / 2013 to August / 2014, using gill nets and electrofishing in 25 points of sampling through the Iguaçu River and tributaries. The food items were grouped in large trophic groups and food habits of each species was categorized from the group with the highest volume. The overlap of the diet was calculated by Pianka index. To identify possible differences in the consumption of trophic groups, PERMANOVA and the Tukey test were used to identify which species differ in the feeding. The SIMPER test was used to determine which group contributed to the difference in consumption between species. Also it was made a NMDS analysi to check the spatial influence in resource consumption between the Iguaçu rivers environments , preserved environments and non-preserved environments , tested by PERMANOVA. We analyzed 873 stomachs of Astyanax and species were classified as algivores (A. minor and A. dissimilis) algivores with herbivory trend (A. bifasciatus) frugivores (A. altiparanae and A. gymnodontus) and insectivores with herbivory trend (A. gymnogenys). The food overlap between pairs of species was intermediate to high. The dietary overlap tested by PERMANOVA showed that there are significant differences between diet of species of Astyanax (F = 2.97, p <0.01) and the Tukey test showed that the diet is different from A. altiparanae diets of other species, except A. gymnogenys. The diet of A. bifasciatus differs from all species. Already, diet of A. gymnodontus is different only of A. minor. The SIMPER test showed 83.62% of dissimilirity in consumption of trophic groups, and the trophic group of Algae and Plant Land and Fruit/Seed were the main contributors. The spatial influence evaluated by NMDS analysis recommended the first two dimensions (0.27 Stress) to explain the higher spatial variance (50%) consumed between trophic groups. The result of PERMANOVA indicated significant differences between environments (F = 1.55; p <0.01) and between species (F = 1.03; p <0.01). Thus, we assume that the species of Astyanax belong to different trophic groups consuming proportions varied of food resources available in the aquatic environment, enabling the coexistence of species of Astyanax in the Lower Iguaçu River.